Survival analysis of female breast cancer patients in Panyu District - YOU Na, LIANG Xiaoxian, LAI Chunyan, RUAN Huihong (预防医学)
Objective: To investigate the survival rate of female breast cancer patients in Panyu District, Guangzhou City, so as to provide the basis for improving the prognosis of breast cancer patients. Methods: Basic information including age, clinical stage and surgical treatment of female breast cancer patients registered in Panyu District and diagnosed in 2017 were collected through the Guangzhou Municipal Cancer Registration and Reporting Management System, and were followed up until December 31, 2022. The survival rate was calculated using the life table. Factors affecting survival time among female breast cancer patients were analyzed using a multivariable Cox proportional hazard regression model. Results: A total of 227 female breast cancer patients were reported in Panyu District in 2017, and had a median age of 51 (interquartile range, 17) years. There were 43 cases (18.94%) in stage Ⅰ, 55 cases (24.23%) in stage Ⅱ, 63 cases (27.75%) in stage Ⅲ, 27 cases (11.89%) in stage Ⅳ, and 39 cases (17.18%) with unknown staging. Surgical treatment was performed in 204 cases (89.87%), and chemotherapy was administered in 73 cases (32.16%). By December 31, 2022, there were 40 deaths and 14 patients lost to follow-up. The one-year, three-year and five-year survival rates were 96.44%, 87.45% and 82.87%, respectively. Multivariable Cox proportional hazard regression analysis showed that older age (HR=1.023, 95%CI: 1.002-1.046), clinical stage Ⅲ (HR=10.050, 95%CI: 1.324-76.270) or IV (HR=42.663, 95%CI: 5.588-325.742) were associated with a higher risk of mortality in female breast cancer patients, while surgical treatment (HR=0.278, 95%CI: 0.130-0.598) was associated with a lower risk of mortality. Conclusions: The five-year survival rate of female breast cancer patients in Panyu District was 82.87%. Age, clinical stage and surgical treatment were the main influencing factors for the survival time of female breast cancer patients.